Borrowing Hydrogen for Organic Synthesis - Reed-Berendt, Benjamin G. (ACS Cent Sci, 2021)
[Image: see text] Borrowing hydrogen is a process that is used to diversify the synthetic utility of commodity alcohols. A catalyst first oxidizes an alcohol by removing hydrogen to form a reactive carbonyl compound. This intermediate can undergo a diverse range of subsequent transformations before the catalyst returns the “borrowed” hydrogen to liberate the product and regenerate the catalyst. In this way, alcohols may be used as alkylating agents whereby the sole byproduct of this one-pot reaction is water. In recent decades, significant advances have been made in this area, demonstrating many effective methods to access valuable products. This outlook highlights the diversity of metal and biocatalysts that are available for this approach, as well as the various transformations that can be performed, focusing on a selection of the most significant and recent advances. By succinctly describing and conveying the versatility of borrowing hydrogen chemistry, we anticipate its uptake will increase across a wider scientific audience, expanding opportunities for further development.